A Critical Analysis Of Narrative Strategy In Priority Tourism Destinations: The Case Of Borobudur - Akhmad Munim; Reni Amelia (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2026)
The transformation of global tourism requires destination management strategies that extend beyond physical development toward the orchestration of symbolic and narrative resources. In the Borobudur Super Priority Destination (DSP), narrative serves as a strategic asset that shapes destination identity, competitiveness, and sustainability. However, fragmented institutional coordination, top-down storytelling, limited community participation, and weak integration of digital naratives have created a gap between policy aspirations and local cultural realities. This study adopts a qualitative policy-oriented case study approach centered on Regulation of the President of the Republic of Indonesia Number 88 of 2024 on the Borobudur–Yogyakarta–Prambanan (BYP) National Tourism Destination Master Plan. The analysis combines qualitative document analysis with an integrative review of Scopus-indexed literature on tourism storytelling, organizational ambidexterity, resource orchestration, and destination governance. The findings reveal that the disconnection between policy design, institutional orchestration, and local meaning-making processes leads to narrative fragmentation, weakening destination competitiveness and authenticity. In response, this paper proposes the Ambidextrous Narrative Orchestration framework, which conceptualizes destination competitiveness as the outcome of dynamic interactions among ambidextrous governance, narrative strategic assets, and adaptive resource orchestration. The study contributes theoretically by extending ambidexterity and orchestration perspectives to culture-based tourism narrative management, while offering practical insights for collaborative, narrative-driven tourism governance.